Understanding and Using Psychology in Mediation - Chackes , Ken; Kirn, Kim L.; Janjalashvili (Translator), Rusudan (Alternative Dispute Resolution Yearbook, 2022)
The paper is a translation of a letter by Ken Chackes and Kim Kirn from the publication: Chackes K., Kirn K.L., Understanding and Using Psychology in Mediation, St. Louis Bar Journal Vol 67, No. 4 Spring 2021, <https://kimlkirnlaw.com/understanding-and-using-psychology-in-mediation/> [12.12.2022]. The translation from English was performed by Rusudan Janjalashvili (Intern of Ivane Javakhishvili Tbilisi State University National Center for Alternative Dispute Resolution).